2019
DOI: 10.1038/s41558-018-0386-4
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns and dynamics of climate–groundwater interactions

Abstract: Groundwater is the largest available store of global freshwater , upon which more than two billion people rely 2. It is therefore important to quantify the spatiotemporal interactions between groundwater and climate. However, current understanding of the global scale sensitivity of groundwater systems to climate change 3,4-as well as the resulting variation in feedbacks from groundwater to the climate system 5,6-is limited. Here, using groundwater model results in combination with hydrologic datasets, we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
253
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(264 citation statements)
references
References 53 publications
10
253
0
1
Order By: Relevance
“…Higher rainfall projected for the OND season is likely to increase groundwater recharge in the eastern and south eastern portions of the basin because groundwater in humid areas is sensitive to increased rainfall, though it is modified by the predominant land use/land cover [62]. Although basin scale studies are rare, regional scale studies using Gravity Recovery and Climate Experiment (GRACE) satellites have shown that the total water storage (lake and groundwater) in the LVB is positively correlated with rainfall and rainfall anomalies associated with ENSO and IOD [28,63].…”
Section: Impact Of Climate Change and Variation On River Discharge Anmentioning
confidence: 99%
“…Higher rainfall projected for the OND season is likely to increase groundwater recharge in the eastern and south eastern portions of the basin because groundwater in humid areas is sensitive to increased rainfall, though it is modified by the predominant land use/land cover [62]. Although basin scale studies are rare, regional scale studies using Gravity Recovery and Climate Experiment (GRACE) satellites have shown that the total water storage (lake and groundwater) in the LVB is positively correlated with rainfall and rainfall anomalies associated with ENSO and IOD [28,63].…”
Section: Impact Of Climate Change and Variation On River Discharge Anmentioning
confidence: 99%
“…Groundwater is the largest source of available freshwater (Gleeson et al ). The assessment of global groundwater resources has been the subject of multiple studies recently, including impacts of groundwater abstractions (Wada et al ) and climate change (Portmann et al ; Cuthbert et al ). Furthermore, global hydrological models (GHMs) started to replace their bucket‐like linear groundwater storage models with (hydraulic) head gradient‐based models to better represent the interaction between surface water and groundwater as well as lateral and vertical flows, including capillary rise (de Graaf et al , , ; Reinecke et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The modern pattern of water availability, including the steep east‐west midlatitude moisture gradient, is a departure from the mean of the late Quaternary, if not the past ~0.8–2.3 million years of repeated glaciation. The geological novelty of the current hydrologic state has implications not only for future water security but also for past ecological dynamics (Jackson & Blois, ), transience and response times in present‐day groundwater systems (Cuthbert et al, ), and the long‐term evolution of North America's critical zone under an often drier‐than‐modern state with moisture gradients different than today (Anderson et al, ; Brantley et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Ice sheet and proglacial-lake areas are shown in light and dark gray, respectively, and the change in ice sheet and proglacial-lake areas between timesteps are shown in light blue and gray-blue, respectively. state has implications not only for future water security but also for past ecological dynamics (Jackson & Blois, 2015), transience and response times in present-day groundwater systems (Cuthbert et al, 2019), and the long-term evolution of North America's critical zone under an often drier-than-modern state with moisture gradients different than today (Anderson et al, 2019;Brantley et al, 2017).…”
Section: Geophysical Research Lettersmentioning
confidence: 99%